Glycated Albumin for the Diagnosis of Diabetes in US Adults. (3rd March 2022) - Fang, Michael; Daya, Natalie; Coresh, Josef; Christenson, Robert H; Selvin, Elizabeth
Abstract: Background: There is growing interest in using glycated albumin for the diagnosis of diabetes, especially when standard tests (glucose and hemoglobin A1c [Hb A1c ]) are unavailable. However, it is unknown how well glycated albumin identifies diabetes in the general population. Methods: We measured glycated albumin in stored serum samples from the 1999–2004 National Health and Nutrition Examination Survey. We evaluated the ability of glycated albumin to identify undiagnosed diabetes in US adults aged ≥20 (n = 4785), overall and at thresholds corresponding to clinical cut points for Hb A1c and fasting plasma glucose (FPG). We assessed 4 reference definitions for undiagnosed diabetes: increased FPG (≥126 mg/dL) [≥6.99 mmol/L), increased Hb A1c (≥6.5%), either FPG or Hb A1c increased, or both FPG and Hb A1 c increased. Results: Among US adults, glycated albumin had excellent diagnostic accuracy across all 4 definitions of undiagnosed diabetes, with the area under the receiver operating characteristic curve (AUC) ranging from 0.824 to 0.951. Performance was generally consistent across patient demographic and clinical characteristics. Glycated albumin cut points of 16.5% and 17.8% were equivalent to an FPG of 126 mg/dL (6.99 mmol/L; 97th percentile) and Hb A1c of 6.5% (98th percentile) and had low to moderate sensitivity (0.273 to 0.707) but high specificity (0.980 to 0.992) for detecting undiagnosed diabetes. Conclusion: The excellent diagnostic performance of glycated albumin to identify diabetes defined by either FPG or Hb A1 c suggests that glycated albumin may be useful for identifying adults with undiagnosed diabetes when standard tests are unavailable.